SOCIO-ECONOMIC MODERNIZATION OF TECHNOGENIC SOCIETY: BACKGROUND AND DEVELOPMENT (Revista Inclusiones, 2019)
When technogenic society is studied, it is often referred to developing and modernizing countries that are undergoing transitional socio-economic processes and go through the stages of radical transformation of political structures. At the same time, it is often overlooked that the developed Western states also went through periods of modernization, which included evolutionary and revolutionary transformations. Nowadays, despite the presence of a relatively stable technogenic political system, from time to time they have to undergo socio-economic and political-institutional changes, sometimes even of a crisis nature. American political scientists B. Brown and R. Macridis note that "political change is not limited to developing countries". All technogenic societies undergo a fairly rapid evolution, including those that are commonly called developed industrial countries, since any political process is closely linked to changes.